KADAR KOLESTEROL DAN β-KAROTEN TELUR ITIK DARI BEBERAPA LOKASI BUDI DAYA ITIK DI JAWA - Saty, Laras; Praseno, Koen; Kasiyati, Kasiyati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
This reasearch about cholesterol and β-caroten contens in the duck’s egg from several duck breeders in central of Java aims to find out the effect of cultivation management on cholesterol and β-caroten. The use of this research to add knowledge about important role of cholesterol and β-caroten which is contained in duck egg toward body function. Sample collection of duck egg implemented at four breeder in Java, that are Cirebon (Rambon duck), Brebes (Tegal duck), Magelang (Magelang duck) and Mojokerto (Mojosari duck). Egg quality measurement implemented in Laboratory Biology Structure and animal function, Department of Biology, Diponegoro University and Wahana Laboratory. The method applied in this research was egg collected in each area. The paremeter that observed was duck weight, woof type, egg weight, cholesterol and β-caroten content of egg. The data that obtained then analyzed by using Analysis of Varience (ANOVA), based on RAL. If there were differences between the treatment, then continued by next assay that was using Duncan assay with 95% significance level. Based on feeding management in four duck breeder, that were, duck breeder in A area gave Eichornia crassipes as additional woof, B area gave Ipomoea aquatica as additional woof, C area gave corn (Zea mays) as additional woof, and D area gave shrimp (Penaeidae Sp.) as additional woof, that was showed real differences between four duck breeder toward cholesterol and β-caroten content of duck egg. Based on the result, can be concluded that woof difference in four duck breeder in Java, also produce different cholesterol and β-caroten content.